Aryl bis-sulfonamides bind to the active site of a homotrimeric isoprenoid biosynthesis enzyme IspF and extract the essential divalent metal cation cofactor. Issue 27 (26th June 2018) - Root, Katharina; Barylyuk, Konstantin; Schwab, Anatol; Thelemann, Jonas; Illarionov, Boris; Geist, Julie G.; Gräwert, Tobias; Bacher, Adelbert; Fischer, Markus; Diederich, François; Zenobi, Renato
Abstract : Native ESI-MS delivers unprecedented insight into unknown homomeric protein binding mechanisms involving complex, multistage binding equilibria with cofactors and ligands. Abstract : Characterizing the mode of action of non-covalent inhibitors in multisubunit enzymes often presents a great challenge. Most of the conventionally used methods are based on ensemble measurements of protein–ligand binding in bulk solution. They often fail to accurately describe multiple binding processes occurring in such systems. Native electrospray ionization mass spectrometry (ESI-MS) of intact protein complexes is a direct, label-free approach that can render the entire distribution of ligand-bound states in multimeric protein complexes. Here we apply native ESI-MS to comprehensively characterize the isoprenoid biosynthesis enzyme IspF from Arabidopsis thaliana, an example of a homomeric protein complex with multiple binding sites for several types of ligands, including a metal cofactor and a synthetic inhibitor. While standard biophysical techniques failed to reveal the mode of action of recently discovered aryl-sulfonamide-based inhibitors of At IspF, direct native ESI-MS titrations of the protein with the ligands and ligand competition assays allowed us to accurately capture the solution-phase protein–ligand binding equilibria in full complexity and detail. Based on these combined with computational modeling, we propose a mechanism of At IspF inhibition by aryl bis-sulfonamides that involves both the competition with the substrate for the ligand-binding pocket and the extraction of Zn 2+ from the enzyme active site. This inhibition mode is therefore mixed competitive and non-competitive, the latter exerting a key inhibitory effect on the enzyme activity. The results of our study deliver a profound insight into the mechanisms of At IspF action and inhibition, open new perspectives for designing inhibitors of this important drug target, and demonstrate the applicability and value of the native ESI-MS approach for deep analysis of complex biomolecular binding equilibria.